Structural behavior of interlocking mortarless putra block wall system - Safiee, Nor Azizi (2011)
The masonry industry has undergone changes where designers now have a variety of choices from the types of block to types of construction. Traditional bonded masonry system can now be replaced with mortarless masonry systems. Interlocking block mortarless wall systems can be defined as walls made of assemblages of interlocking block unit without use of any mortar or adhesive material at interlayer between courses. However, the structural behavior of interlocking block mortarless wall has not yet been completely explained. The structural behavior and design parameters for this system are expected to be different than the conventional wall system. In order to understand the performance of the wall system, the behavior and important design parameters of walls under different loadings need to be determined and identified. This study was primarily conducted through experimental investigation and finite element analysis. A total of 21 full scale specimens were used to observe the behavior and response of three different groups of interlocking mortarless wall systems namely walls without opening, walls with openings and walls with pilasters. For walls without opening, the experimental investigation was carried out under inplane and out-of-plane loading. Whereas for the other two groups, they were investigated under compressive loading only. A parametric study using finite element analysis was carried out to study the effect of different parameters on each interlocking wall group considered in addition to the existing data. The finite element program used was developed using the Fortran language while considering important features of the interlocking block mortarless interface. Four different models were developed to represent the different wall systems in this study. Results obtained from the simulation were validated with the corresponding experimental results to check its appropriateness and accuracy. The validation study revealed the finite element results based on the proposed models were in good agreement with the experimental results. The wall specimens under in-plane and out-of-plane loads were tested under constant pre-compressive vertical load and increasing lateral load. The maximum lateral load carrying capacity, development of strain and failure characteristics were recorded. In the in-plane case, shear stress capacity of the wall became a major concern in this observation. Failure of the in-plane wall is controlled by diagonal shear failure and moderate toe crushing. The main outcome from this in-plane wall investigation was the relationship between average pre-compressive stress and shear stress at failure. For walls under out-of-plane load, the results indicated that pre-compressive vertical loads and reinforcement significantly affected the structural behavior of interlocking block mortarless walls. The failure of wall was dominated by opening between dry joint, cracking, flexure deflection and toe crushing. The design of walls under out-ofplane was controlled by dry joint opening mechanism at mid height of the wall. Wall panels with opening were tested under vertical compressive loading taking into consideration different sizes of opening and slenderness ratio. The results revealed that the opening size would reduce the maximum load carrying capacity of the wall. The location of openings within the wall also affected the behavior of the wall with opening. The test results of walls with pilaster revealed that the slenderness ratio had significant effect on the load carrying capacity. The pilasters may also increased the lateral resistance with respect to the out-of-plane displacement and load carrying capacity of the wall systems. By adding pilasters to the wall system failure may be delayed in comparison to that expected to occur in similar specimens of walls without pilaster. The results indicate that pre-compressive load and slenderness ratio has a significant effect on walls under combined loading. While for other wall groups (wall with opening and wall with pilaster) which were primarily subjected to compressive vertical loads, the slenderness ratio and size opening were factors affecting the behavior of wall systems. The effect of the important parameters contributed to the behavior and prediction of strength for each groups of mortarless interlocking wall system considered. As a contribution, a few formulae, tables and curves were proposed to be used in predicting the ultimate strength of interlocking mortarless Putra block wall system according to their loading condition on each group of wall system. Finally, with a deeper understanding of the behavior of mortarless masonry wall systems, it may contribute to a better application of design and construction.